2011
DOI: 10.9755/ejfa.v23i1.5315
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of treated sewage wastewater for green forage production in<br>a hydroponic system

Abstract: Using alternative water resources such as tertiary treated sewage wastewater is considered very important to produce crops (e.g., green forage) due to irrigation water shortage, especially in arid and semiarid regions like Jordan. Moreover, growing forage hydroponically is now becoming popular in drought prone areas to produce green fodders in large quantities with less water use. The objectives of this study were to investigate the effects of irrigation with tertiary sewage treated wastewater (WW), tap water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Wastewater not only fulfills the irrigation requirements but also partially satisfies the nutritional requirement of crop plants. Resultantly, it reduces farmers' cost of production (Jiménez, 2005;Al-Karaki, 2011). More than 80% of the farmers were aware of health-related issues, but they preferred to apply wastewater for irrigation.…”
Section: Background Of Waste Water Preferencementioning
confidence: 99%
“…Wastewater not only fulfills the irrigation requirements but also partially satisfies the nutritional requirement of crop plants. Resultantly, it reduces farmers' cost of production (Jiménez, 2005;Al-Karaki, 2011). More than 80% of the farmers were aware of health-related issues, but they preferred to apply wastewater for irrigation.…”
Section: Background Of Waste Water Preferencementioning
confidence: 99%
“…Hydroponic barley (Hordeum vulgare) production using wastewater has been investigated [13] and found a decrease in yields of 47% and 17% for conventional activated sludge and lagoon system water compared to half-strength Hoagland Solution, concluding that further fertilization with wastewater would be necessary and that metal(loid) concentrations in plant tissue increased, but did not exceed, toxic levels. Al-Karaki [14] explored using tertiary-treated sewage wastewater to grow barley in controlled environment vertical hydroponic growing towers. Compared to treatments of tap water alone, which was used without fertilizer for hydroponic green fodder due to short growth period, wastewater, and wastewater mixed with municipal tap water improved both yields and water efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The variables that most influence the development of the TC of the HGF are temperature and humidity. In the literature, several studies have been carried out under different conditions of controlled temperature and relative humidity, depending on the application-for example, 21-25 • C and 65-75%RH [42]; 22-26 • C and 50-73%RH [43]; 23-25 • C and 6-70%RH [44]; 18-21 • C and 70%RH [45]. In such studies are reported yields of 7-12 kg of wet HGF per kilogram of harvested seed.…”
Section: Internal Conditions Of the Gchmentioning
confidence: 99%